Evaluating Maternal Social Support in Low Birth Weight Neonates Comparing With Normal Neonates in 2012: - Kazemi, Reza; Riahinejad, Soheila; Farhangfar, Behrouz; Arabi, Marzieh (Galen Medical Journal, 2014)
Introduction: Pregnancy as a stressful event may cause some consequence for both mother and infant such as low birth weight (LBW). LBW is seen in about 7% of pregnancies in Iran. It was proved there is a correlation between infants weight and maternal social support. This study was designed to evaluate maternal perceived social support in LBW infants and infants with normal weight. Methods and Materials: This was a case-Control study which was done in Isfahan, Iran during April-November 2012 on 188 participants in 2 groups. In case group we had evaluated mothers with low birth weight infants and control group were mother with normal infants. Farsi version of Multidimensional Scale of Perceived Social Support (MSPSS-P) was used for social support evaluation. Results: In LBW group mean family support subscale score was 14.87 ± 4.33, Mean friends support subscale score was 9.65 ± 5.89 and significant others support subscale mean score was 15.18 ± 5.11. In normal weight group mean family support subscale score was 18.46 ± 3.98, Mean friends support subscale score was 15.4 ± 6.41 and significant others support subscale mean score was 18.46 ± 4.1. Conclusion: Maternal perceived prenatal social support could be a predictor for infants birth weight. Supportive family could helps pregnant women to reduce adverse pregnancy out comes such as low birth weight.